The Longitudinal Relationship Between Social Support and Physical Activity in Hispanics. Issue 6 (July 2019) - Heredia, Natalia I.; Walker, Timothy J.; Lee, MinJae; Reininger, Belinda M.
Purpose: Social support has been identified as a determinant of physical activity (PA), but research has been primarily cross-sectional, with mixed findings for different Hispanic subgroups and limited longitudinal research with Hispanics. The purpose of this study is to assess the longitudinal associations of social support with PA in Hispanics on the Texas-Mexico Border. Design and sample: We used 2 time points of data collected from Hispanic adults in the Cameron County Hispanic Cohort (N = 588). Measures: We collected social support for PA and self-reported leisure-time PA. Analysis: We used cross-lagged panel models to assess the association between friend support, family support, family punishment (criticizing or complaining) and PA over time. Results: Although social support overall was low for PA, fully adjusted cross-lagged panel models indicated that time 1 friend support was associated with time 2 PA (adjusted rate ratio = 1.02, 95% confidence interval = 1.00 -1.04), though family support was not associated with time 2 PA. In males, time 1 friend support was inversely associated with time 2 family punishment. Conclusion: As expected, the directionality of the relation appears to be from social support to PA. Friend support appears to be predictive of PA in Hispanics, whereas family support is not. This should be considered in intervention development, particularly because familismo (commitment and mutual obligation to family) is considered to be a strong value in these communities.